The Use of Antihypertensive Drugs as Coadjuvant Therapy in Cancer - Carlos-Escalante, José A.; de Jesús-Sánchez, Marcela; Rivas-Castro, Alejandro; Pichardo-Rojas, Pavel S.; Arce, Claudia; Wegman-Ostrosky, Talia (Frontiers in Oncology, 2021)
Cancer is a complex group of diseases that constitute the second largest cause of mortality worldwide. The development of new drugs for treating this disease is a long and costly process, from the discovery of the molecule through testing in phase III clinical trials, a process during which most candidate molecules fail. The use of drugs currently employed for the management of other diseases (drug repurposing) represents an alternative for developing new medical treatments. Repurposing existing drugs is, in principle, cheaper and faster than developing new drugs. Antihypertensive drugs, primarily belonging to the pharmacological categories of angiotensin-converting enzyme inhibitors, angiotensin II receptors, direct aldosterone antagonists, β-blockers and calcium channel blockers, are commonly prescribed and have well-known safety profiles. Additionally, some of these drugs have exhibited pharmacological properties useful for the treatment of cancer, rendering them candidates for drug repurposing. In this review, we examine the preclinical and clinical evidence for utilizing antihypertensive agents in the treatment of cancer.